UTILIZATION OF SAMANYA SHODHANA IN THE PURIFICATION OF EXCESS MERCURY OBTAINED FROM DENTAL OPERATORY- A PRELIMINARY STUDY - Pandiar, *Deepak; Chand Baranwal, Harakh; Chattopadhyay, Kausik; Choudhary, Anand Kumar; Ganesan, Vellaichamy; Kumar Sonkar, Piyush (International Journal of Ayurveda and Pharma Research, 2018)
Background: Concerns about toxicity of mercury and disposal of excessive mercury has led to decreased usage of mercury in dental profession but still tooth colored restorative materials are not affordable by all the classes of any society. The disposal of excess mercury has always been a matter of concern. Thus, in the present study, we attempted to evaluate a simple procedure from Rasa Shastra using lime powder, garlic and rock salt for recycling of excess mercury obtained from dental operatory.Materials and methods: The excess mercury was recycled by the standard procedure explained in Ayurveda texts (Samanya shodhana) using Sudha churna (lime powder), Lashuna kalka (paste of Allium sativum L.) and Saindhava lavanaa (rock salt). The commercially available mercury and recycled mercury was analyzed by inductively coupled plasma mass spectrometry (ICP-MS) for the detection of elements in ppm level.Results: It was found that the excess impure mercury contained 5138 ppm, 2866.1 ppm and 0.371 ppm of Silver, Copper and Tin respectively. After Shodhana, the level of silver, tin and copper were markedly reduced. Purified mercury showed a level of 119.5ppm silver, 0.5324 ppm copper and 0.3233 ppm tin.Conclusion: Samanya shodhana is a simple promising procedure which can be used for mercury recycling. The procedure doesnot require sophisticated equipments and maneuver. Further, the materials used in the procedure are easily available and affordable at low cost.